RAGAM TUBUH IDEOLOGIS: REPRESENTASI KELELAKIAN DAN KEPEREMPUANAN DALAM IKLAN DI MEDIA CETAK - Setiawan, Ikwan (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2018)
The media industry opens shared access to man and woman in pursuing their career. The contestation of woman in media is perceived to be the liberation against the patriarchal ideology. The perception cannot be separated from the discourses of the pubic. Man, since thousand years ago, has been viewed to be more logic and superior than his counterpart. Woman is believe to have no ability to use his logics more than her heart and emotion. This paper tries to focus on the images of woman represented by the advertisement. Employing the foucault’s discourse theory and Roland Barthes’s semiotic of myth, it is aimed to disclose how woman represented and the ideology works underlying the representation. The analysis shows that the ads in the mass media cannot be blamed to be the means to maintain the patriarchal hegemony only. The ads, in fact, are the representation arena pursued by the competing forces of discourse in the society. They, besides functioned to market the product, may provide and offer some ideological content. It means the ads cannot be whole-generalized to be the patriarchal media : they than have a potential subversive shocking the hegemonic ideology. The feminist discourse evoke in the ads offers the strategic role of woman in the contestation. In sum, the bodies of woman in the ads are the fragmented ideological bodies slice by the negotiation of varying discourses of ideology developing in the society.